OBSERVATIONS OF A CPA EXAMINER. - Forbes, John F. (The Accounting Review, 1944)
Abstract In this article the author, as a CPA examiner presents information about accountants. In Great Britain and her dependencies, the Institutes of Chartered Accountants, and similar societies, are organized to promote and control the profession, and with them, naturally, the profession holds the first place of interest. But the chartered accountant holds no certificate from the state. There are any number of accounting organizations which claim to possess as high standards as those of the Institutes, and they may assert this fact to the public in a manner which would be illegal in many of the states of this country if applied to the CPA. The most important thing that a member of California state board has to have in mind is the public. Second in importance as a matter of state board concern is the person who happens to be an applicant for a CPA certificate. He has certain rights which cannot be infringed upon with impunity, and these rights may be summarized generally in the expression a fair deal.